Behaviour of flexible piles subjected to inclined loads. (September 2015) - Conte, E.; Troncone, A.; Vena, M.
Abstract: The behaviour of the piles under inclined loads is a topic not fully investigated in the literature. No experimental results from full-scale pile tests are available so that numerical analysis can be an interesting tool to provide useful results about the pile behaviour under this loading condition. In this study, a three-dimensional finite element approach is used to analyse the response of reinforced concrete flexible piles to inclined loads. Appropriate constitutive models are adopted to account for the nonlinear behaviour of the pile and the soil. In particular, the occurrence of plastic strains in the soil, concrete cracking and steel yielding in the pile as well as the occurrence of slip and gap at the pile–soil interface are adequately modelled. To assess the reliability of the method, some loading tests documented in the literature concerning axially or laterally loaded piles are first simulated. A fairly good agreement is found between numerical and experimental results. The geotechnical model and the pile from the above-mentioned tests are considered to highlight some characteristic aspects of the response of flexible piles to inclined loads. In particular, the analysis results show that a flexible pile can experience a flexural or an axial behaviour depending on the load inclination. Load inclination also influences significantly both the stiffness and the bearing capacity of the soil–pile system. Comparisons with the results from some empirical solutions proposed in the literature to evaluate the bearing capacity of the piles under inclined loads are also shown.